Topical imiquimod treatment of aciclovir-resistant herpes simplex disease: case series and literature review. Issue 4 (15th March 2011) - Perkins, Nicky; Nisbet, Mitzi; Thomas, Mark
Abstract : Infection with herpes simplex virus (HSV) is extremely common worldwide. In immunocompromised patients anogenital HSV disease may have atypical features and may be very severe. Treatment of aciclovir-resistant anogenital HSV disease is challenging, as resistance to alternative treatments may occur, and effective treatment generally involves intravenous therapy with relatively toxic agents such as foscarnet. This case report presents three immunocompromised patients with presumed aciclovir-resistant anogenital HSV disease who were successfully treated with topical imiquimod. Imiquimod promotes local immune activation, which results in resolution of viral lesions such as anogenital warts and HSV disease. It is convenient to use and avoids the necessity for intravenous treatment with substantial systemic toxicity. In addition, as the mode of action of imiquimod is related to immune stimulation rather than direct antiviral activity, it may be used repeatedly without resistance developing.